PENDIDIKAN ANTIKORUPSI SEBAGAI SOLUSI DALAM MEWUJUDKAN MASA DEPAN BANGSA YANG BERSIH DAN BERINTEGRITAS - Lisa Citra Anggraini; Diana Dinata (Kampus Akademik Publiser, 2026)
Corruption is a serious problem that can hinder development and damage the social and political order of a nation. It not only causes economic losses but also reduces public trust in the government and weakens moral values. Therefore, comprehensive and sustainable efforts are needed to prevent corruption, one of which is through anti-corruption education. This study aims to examine the role of anti-corruption education as a solution in realizing a clean and integrity-driven future for the nation. The method used is a literature study by analyzing various journals, books, and other relevant academic sources. The results show that anti-corruption education is effective in instilling values of integrity such as honesty, responsibility, fairness, and social awareness. Through the systematic implementation of committed to rejecting all forms of corruption. Thus, anti-corruption education becomes a strategic solution in creating a clean, just, and integrity-based future for the nation